Child Protection Case Analysis: an epistemological universe for social intervention - González Abad , Libertad; Rodríguez Rodríguez, Alfonsa (Interacción y Perspectiva, 2024)
This theoretical-reflexive article aims to offer a sufficiently rich epistemological framework with which to approach the complexity of cases assisted by child protection services in Madrid. Thus, through a paradigmatic case analysis, product of a professional supervision process, each of the intervention maps are reviewed: the systemic, the constructivist, the social constructionist and the post-structural. Supervision is presented as a second-order research method, associated with action-research-reflection. Through supervision, one gains awareness of one’s own actions and thoughts, and broadens the range of possibilities for intervention. Accordingly, the case is presented throughout the text from the different maps indicated. Thus, a multidimensional perspective is adopted, required to create a dynamic of analysis that overcomes the classic dichotomies of social work. This process of supervision and case analysis illustrates, as main result, the significant cost for professional practice of accepting excluding positions, which tend to oppose the individual to the community; the therapeutic to the control, the material to the emotional, the technical to the mundane, etc. This dichotomous acceptance reduces the possibilities of intervention related to the unsaid, the non-categorizable and the non-fragmentable. Finally, this proposal is not only a technical, but also an ethical-political response to strengthen the reflective practice and education of social work, avoiding the perverse effects that the managerialist approach of the discipline has on the profession, and more specifically on child protection practices.